Merchant ships at war the Falklands experience - Villar, Roger (Naval Institute Press, 1984)
In the first detailed study of the merchant ships directly employed in the 1982 Falklands War, Captain Villar analyses one of the most astounding aspects of the whole campaign - the requisition, conversion, and deployment of a highly varied fleet of nearly 50 merchantmen.